Galatians: worship for life by faith in the crucified and risen Lord - Heil, John Paul (Wipf and Stock Publishers, 2019)
Intro -- Title Page -- Abbreviations -- Chapter 1: Introduction -- Chapter 2: Galatians 1:1-10 -- Chapter 3: Galatians 1:11-24 -- Chapter 4: Galatians 2:1-14 -- Chapter 5: Galatians 2:15-21 -- Chapter 6: Galatians 3:1-5 -- Chapter 7: Galatians 3:6-16 -- Chapter 8: Galatians 3:17-29 -- Chapter 9: Galatians 4:1-7 -- Chapter 10: Galatians 4:8-20 -- Chapter 11: Galatians 4:21-31 -- Chapter 12: Galatians 5:1-13 -- Chapter 13: Galatians 5:14-26 -- Chapter 14: Galatians 6:1-18 -- Chapter 15: Conclusion -- Bibliography.